▾Sustained-release formulations of metoclopramide. Issue 7 (5th April 1988) - Unknown
Abstract : Metoclopramide has been in clinical use for symptomatic relief of nausea, vomiting and gastro-oesophageal reflux for 20 years. About 1½ million prescriptions are written for it each year in general practice. It has recently been marketed in two new sustained-release formulations.